Influence of different surface treatments of fiberglass posts on the bond strength to dentin - Bruna Cristina do Nascimento Rechia; Ruth Peggy Bravo; Naylin Danyele de Oliveira; Flares Baratto Filho; Carla Castiglia Gonzaga; Carmen Lucia Mueller Storrer (Universidade Estadual de Campinas, 2017)
Aim: To assess the influence of different fiberglass post surface treatments on the bond strength (BS) to root dentin. Methods: Thirty bovine root canals were endodontically treated and filled with gutta-percha and AH Plus sealer. At 24 h after the endodontic filling, the post spaces were prepared with Gates-Glidden drills and #3 drills of the DC White Post system, maintaining a 4 mm apical seal. The roots were randomly divided into three groups: S (fiberglass posts treated with silane), SA (fiberglass posts treated with silane and a hydrophobic adhesive system) and SHA (fiberglass posts treated with silane, followed by drying with hot air). The posts were cemented with a selfadhesive cement (RelyX U200). The specimens were stored in distilled water at 37 °C for 24 h and subjected to the push-out test (0.5 mm/min). Data were statistically analyzed using one-way ANOVA and Tukey's test (α=0.05) Results: SA and SHA groups showed the highest BS mean values (11.29 and 10.85 MPa, respectively), while the S group presented the lowest BS mean value (7.21 MPa). S group was significantly different from SA and SAH groups. Conclusions: The surface treatment of fiberglass posts influenced BS values.